Estimating the impact of achieving Turkey's non-communicable disease policy targets: A macro-simulation modelling study - João Breda; Luke N Allen; Birol Tibet; Toker Erguder; Erdem Karabulut; Hasan H Yildirim; Alexander Mok; Kremlin Wickramasinghe (Elsevier, 2021)
Summary: Background: The Burden of non-communicable disease (NCDs) has continued to rise globally, particularly in low- and middle-income countries. In Turkey, NCDs account for 89% of all deaths, with nearly one in five deaths occurring before age 70. This study investigates the number of NCD deaths that could be prevented if Turkey met national and international targets for major modifiable NCD risk factors. Methods: Preventable deaths were estimated using the World Health Organization (WHO) 'Preventable Risk Integrated ModEl' (PRIME), by combining: 1) Baseline exposure data for risk factors, referenced from national surveillance and cohort studies; 2) Aetiological associations from published meta-analyses; and 3) Demographic and mortality statistics obtained from the Turkish Statistical Institute (TurkStat). Confidence intervals were estimated using Monte Carlo simulations. Findings: If Turkey met its NCD risk factor targets for reducing tobacco and salt consumption by 30%, and physical inactivity by 10% in 2017, an estimated 19,859 deaths (95%CI: 12,802 to 26,609) could have been prevented. Approximately two thirds of these preventable deaths were in men, and one in three were in adults below 75 years. A 30% relative reduction in the consumption of alcohol, tobacco, and salt, as well as physical inactivity, would prevent 180 (107 to 259); 4,786 (3,679 to 5,836); 13,112 (5,819 to 19,952); and 7,124 (5,053 to 9,212) deaths, respectively. Interpretation: Among major modifiable NCD risk factors, population-level reductions in salt intake and physical inactivity present the greatest opportunity for reducing NCD mortality in Turkey. These findings can help Turkey prioritise interventions to meet the Sustainable Development Goal target of reducing NCD mortality by one third, by 2030.